Diaphragm ruptures - Cazabán, Luis A (Cirugía del Uruguay, 1974)
Diaphragmatic rupture is a pathological condition which is becoming more and more frequent due to automobile accidents. As a rule this occurs in seriously politraumatized patients, with considerable cardiorespiratory distress. These are injuries where diagnosis is difficult and the clinical definition of the lesion is of paramount importance. The authors, referring to their experience of four cases, explained the etiopathogenic factors, clinical evolutio,_ and therapy applied. If necessary thoraxic surgery should be performed. The election of the method of approch depends on the diagnostic localization, Abdominal approach is recommended when associated intra-peritoneal lesions Rre suspected. In the absence of intra-abdominal injury, but with diagnosis of probable diaphragmatic rupture, a thoracotomy is recommended. The closure of the diaphragm should be very carPfully ne with non-absorbable elements. The post operatory management should be the responsibility of the same team that began cardiocirculatory recuperation and perf ,rmed the operatior..